Genetic Analysis of Powdery Mildew Severity over the Environments in Fenugreek (Trigonella fOen1l11l-graeC1l11l L.) - Avtar, R (Annals of Arid Zone, 2016)
Generation mean analysis involving six generations of four crosses of fenugreek (Trigonella foenlllll-graeclIlIl L.) was used to study the inheritance of severity of powdery mildew disease caused by Erysiphe polygoni DC under two different environments, i.e., artificially inoculated with conidia of disease (EI) and natural or uninoculated (E2). The additive-dominance model was found adequate to explain variability in NLM x TS in both EI and E2; and NLM x HM 350, HM 350 x HM 65 and TS x HM 65 in E2 only. Additive effects were pronounced in majority of the crosses. Among epistatic interactions, additive x additive and additive x dominance type were present. Appropriate breeding methodology has been suggested.